2020
DOI: 10.1038/s42003-020-01403-4
|View full text |Cite
|
Sign up to set email alerts
|

ATAC-seq with unique molecular identifiers improves quantification and footprinting

Abstract: ATAC-seq (Assay for Transposase-Accessible Chromatin with high-throughput sequencing) provides an efficient way to analyze nucleosome-free regions and has been applied widely to identify transcription factor footprints. Both applications rely on the accurate quantification of insertion events of the hyperactive transposase Tn5. However, due to the presence of the PCR amplification, it is impossible to accurately distinguish independently generated identical Tn5 insertion events from PCR duplicates using the st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…The accuracy of datasets with a low abundance of RNA was significantly improved ( Yu F. et al, 2018 ). UMI-ATAC-seq technique was integrated into standard ATAC-seq procedures, which can rescue about 20% of reads that are mistaken as PCR duplicates in standard ATAC-seq ( Zhu T. et al, 2020 ). In this study, we counted molecules by the total number of distinct UMIs to quantitatively assess miRNA-seq data, which provided accurate expression patterns of miRNA response to salt stress in cotton.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of datasets with a low abundance of RNA was significantly improved ( Yu F. et al, 2018 ). UMI-ATAC-seq technique was integrated into standard ATAC-seq procedures, which can rescue about 20% of reads that are mistaken as PCR duplicates in standard ATAC-seq ( Zhu T. et al, 2020 ). In this study, we counted molecules by the total number of distinct UMIs to quantitatively assess miRNA-seq data, which provided accurate expression patterns of miRNA response to salt stress in cotton.…”
Section: Discussionmentioning
confidence: 99%
“…The UMI method begins with a reverse-transcription reaction using a primer designed with an anchored polyT and a unique barcode, which enable sequencing reads to be assigned to individual transcript molecules and thus the removal of amplification noise and biases. The quantitative precision of this method is thus improved, especially at low molecule counts ( Islam et al, 2011 ), and UMI method was widely used for high-accuracy ( Zhu T. et al, 2020 ; Karst et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Minghui63 ( O. sativa-MH ), O. sativa cv. Zhenshan97 ( O. sativa-ZS ), Setaria italica , Sorghum bicolor and Zea mays were generated from our previously established protocol ( 25 ) and deposited in NCBI with SRA accession SRP308654.…”
Section: Methodsmentioning
confidence: 99%
“…However, this can induce further biases. By making use of UMIs, one study was able to quantify how many Tn5 insertions may independently occur at the same position [48]. This showed that up to 20% of the reads discarded based on their alignment positions, a standard method step in many protocols, were done so erroneously and actually arose due to independent Tn5 insertion events.…”
Section: Scatac-seqmentioning
confidence: 99%